POSTMENOPAUSAL BLEEDING: CAUSES AND RISK OF GENITAL TRACT MALIGNANCY - Dawood, Nasira Sabiha; Peter, Kiran; Ibrar, Faiza; Dawood, Asif (Journal of Ayub Medical College Abbottabad, 2010)
Background: Postmenopausal bleeding (PMB) is bleeding occurring after 6-12 months of amenorrhea in a woman of age where the menopause can be expected. Objectives of this study were to ascertain various causes and prevalence of genital organ malignancy in patients presenting with postmenopausal bleeding. Methods: A prospective observational study carried out in the Department of Obstetrics and Gynaecology, Fauji Foundation Hospital, Rawalpindi comprising of 167 consecutive cases presenting with postmenopausal bleeding one year after menopause. Women having undergone hysterectomy and bilateral salpingo-oophorectomy, receiving radiotherapy or chemotherapy, suffered trauma to the genital tract, having coagulation disorder or on anticoagulant or hormone replacement therapy were excluded. Detailed history was obtained and a thorough clinical examination was conducted. Data were entered into hospital computer database (Medix„¢) system. Mean±SD were calculated for age, percentage was calculated for types of histopathological findings. Results: The commonest cause of PMB was atrophic endometritis and vaginitis 33 (21.2%). Overall incidence of various genital tract malignancies was 25 (16.0%). Conclusion: The overall incidence of genital tract malignancies in patients presenting with PMB is high (16.0%), therefore, it needs to be taken seriously and requires prompt and thorough investigations. Keywords: Bleeding, postmenopausal, female genital tract, malignancies, prevalence, aetiology